A specific gut microbiota signature is associated with an enhanced GLP-1 and GLP-2 secretion and improved metabolic control in patients with type 2 diabetes after metabolic Roux-en-Y gastric bypass - Hernández-Montoliu, Laura; Rodríguez-Peña, M-Mar; Puig, Rocío; Astiarraga, Brenno; Guerrero-Pérez, Fernando; Virgili, Nuria; López-Urdiales, Rafael; Osorio, Javier; Monseny, Rosa; Lazzara, Claudio; Sobrino, Lucía; Pérez-Maraver, Manuel; et al. (Frontiers in Endocrinology, 2023)
OBJETIVE: To determine changes in incretins, systemic inflammation, intestinal permeability and microbiome modifications 12 months after metabolic RYGB (mRYGB) in patients with type 2 diabetes (T2D) and their relationship with metabolic improvement. MATERIAL-METHODS: Prospective single-center non-randomized controlled study, including patients with class II-III obesity and T2D undergoing mRYGB. At baseline and one year after surgery we performed body composition measurements, biochemical analysis, a meal tolerance test (MTT) and lipid test (LT) with determination of the area under the curve (AUC) for insulin, C-peptide, GLP-1, GLP-2, and fasting determinations of succinate, zonulin, IL-6 and study of gut microbiota. RESULTS: Thirteen patients aged 52.6±6.5 years, BMI 39.3±1.4 kg/m 2 , HbA1c 7.62±1.5% were evaluated. After mRYGB, zonulin decreased and an increase in AUC after MTT was observed for GLP-1 (pre 9371±5973 vs post 15788±8021 pM, P<0.05), GLP-2 (pre 732±182 vs post 1190±447 ng/ml, P<0.001) and C-peptide, as well as after LT. Species belonging to Streptococaceae, Akkermansiacea, Rickenellaceae, Sutterellaceae, Enterobacteriaceae, Oscillospiraceae, Veillonellaceae, Enterobacterales_uc, and Fusobacteriaceae families increased after intervention and correlated positively with AUC of GLP-1 and GLP-2, and negatively with glucose, HbA1c, triglycerides and adiposity markers. Clostridium perfringens and Roseburia sp. 40_7 behaved similarly. In contrast, some species belonging to Lachnospiraceae, Erysipelotricaceae, and Rumnicocaceae families decreased and showed opposite correlations. Higher initial C-peptide was the only predictor for T2D remission, which was achieved in 69% of patients. CONCLUSIONS: Patients with obesity and T2D submitted to mRYGB show an enhanced incretin response, a reduced gut permeability and a metabolic improvement, associated with a specific microbiota signature.